Fishing spaces and ethnoecological knowledge of snook and king mackerel artisanal fishing in southern Espírito Santo – Brazil - Cavalcante Corrêa, Josilene; Musiello Fernandes, Joelson; Albino, Jacqueline (Geografares, 2020)
This paper raises the ethnoecological knowledge of artisanal fishermen from Ubu and Parati, in southern Espírito Santo, in order to understand their strategies for using marine spaces to maintain subsistence and income. Focusing on ethnospecies of snooks and king mackerels, interviews were conducted (n=22) to acquire information on the fishing spaces, behavior of fish, capture techniques, in addition to climatic and oceanographic dynamics that interfere in fishing. Later, this information was correlated with data found in the scientific literature. We conclude, first, that knowledge about the environment allows the fishermen to diversify fishing efforts, techniques and places, provided by the environmental conditions brought every each seasonality. Second, there is a need for specific studies to support local fisheries management, and finally, there is a disagreement about fisheries regulations, considered incompatible with traditional way of working.
Keywords: fishing spaces; traditional fishing; ethnoecological assessment